Prevalence, determinants and knowledge about herbal medicine and non-hospital utilisation in southwest Nigeria: a cross-sectional study - Olujimi Aina; Lata Gautam; Padam Simkhada; Sarah Hall (BMJ Open)
Objectives To examine the prevalence, determinants, safety perceptions, effectiveness and knowledge of herbal medicines (HMs) and reasons for non-hospital utilisation.Design Cross-sectional study.Setting Ekiti state, southwest Nigeria.Participants A representative sample (n=1600) of adults (18 years or above) currently living in Ekiti state, southwest Nigeria for at least 2 years, at the time of study.Results The majority of the respondents (85% n=1265) have used HMs in the last 2 years. Across economic classes use, middle income (88.3%) was the highest (p<0.001), suggesting poverty is not a major factor, even with income inequality. Their use was the most common among respondents with a primary level of education (91.4%, p=0.001); and 100% use (p=0.009) of respondents practising African traditional religion; farmers and those 70 years or above. Our study also reveals more men (p<0.001) used HMs (89.9%) than women (78.6%) and effectiveness was a major reason for use (39.6%) followed by affordability (31.9%). Although the majority of the respondents (90%) knew the difference between certified and uncertified HMs, uncertified ones were the most commonly used (37.3%) in the population.Conclusion Although there is a cultural history of HM use within the study population, the choice of use was based on their effectiveness. Therefore, a scientifically valid analysis of this claim within the study population may help achieve a cheaper and affordable healthcare alternative which will be safe. This is important, considering that uncertified HMs were chosen over certified ones, even though a large majority of respondents were aware of differences and likely consequences. This study highlights the need for further investment by the government, individuals and corporate stakeholders in HM research and improvement of conventional healthcare system. This is in addition to public health awareness on the danger of use of uncertified herbal products.